LEGAL CONSEQUENCES OF THE POSITION OF ACTING REGIONAL SECRETARY EXCEEDS THE TIME LIMIT - Abrari, Achmad; Nailulfari, Fardati (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyse the legal consequences of the position of Acting Regional Secretary (Plh. Sekda) exceeding the stipulated time limit. Based on the provisions of Article 58 Permenpan 22/2021, the term of office of the Plh. Secretary's term of office is limited to a maximum of 30 days, and if it exceeds this time, it can cause legal problems related to the validity of actions taken during the term of office. This research uses the normative juridical method to examine the applicable legal provisions and analyse the potential legal complications that may arise if the Acting Regional Secretary continues to serve beyond the time limit. Secretary continues to serve beyond the regulated time limit. The research findings show that the performance of duties beyond the time limit may affect the validity of administrative decisions and actions, and may trigger legal challenges to the authority exercised. In addition, the research also recommends the importance of appointing an Acting Regional Secretary (Pj. Sekda) in a timely manner to avoid further complications. This research is expected to contribute to the development of policy and management of local government administration in order to prevent procedural errors and legal impacts in the future.